2022
DOI: 10.3390/ijms23169357
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoylation of Voltage-Gated Ion Channels

Abstract: Protein lipidation is one of the most common forms of posttranslational modification. This alteration couples different lipids, such as fatty acids, phospho- and glycolipids and sterols, to cellular proteins. Lipidation regulates different aspects of the protein’s physiology, including structure, stability and affinity for cellular membranes and protein–protein interactions. In this scenario, palmitoylation is the addition of long saturated fatty acid chains to amino acid residues of the proteins. The enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 124 publications
0
13
0
Order By: Relevance
“…Studies have shown that S-palmitoylation can influence the function of cardiac myocytes by regulating ion channels and signal transduction. 136 The important role of S-palmitoylation regulation in ion channel homeostasis and excitation-contraction coupling of cardiac myocytes has been discussed in detail in previous reviews. 136,137 Using the S-palmitoylation of voltage-gated sodium channels (NaVs) as an example, we will briefly discuss its influence on cardiac electrical activity and its implications in heart diseases, highlighting the role of S-palmitoylation in maintaining cardiac homeostasis.…”
Section: Cardiovascularmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that S-palmitoylation can influence the function of cardiac myocytes by regulating ion channels and signal transduction. 136 The important role of S-palmitoylation regulation in ion channel homeostasis and excitation-contraction coupling of cardiac myocytes has been discussed in detail in previous reviews. 136,137 Using the S-palmitoylation of voltage-gated sodium channels (NaVs) as an example, we will briefly discuss its influence on cardiac electrical activity and its implications in heart diseases, highlighting the role of S-palmitoylation in maintaining cardiac homeostasis.…”
Section: Cardiovascularmentioning
confidence: 99%
“…136 The important role of S-palmitoylation regulation in ion channel homeostasis and excitation-contraction coupling of cardiac myocytes has been discussed in detail in previous reviews. 136,137 Using the S-palmitoylation of voltage-gated sodium channels (NaVs) as an example, we will briefly discuss its influence on cardiac electrical activity and its implications in heart diseases, highlighting the role of S-palmitoylation in maintaining cardiac homeostasis. Nav tightly controls the generation and propagation of sodium-dependent action potentials.…”
Section: Cardiovascularmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatty acylation of lysine is a novel mechanism that regulates protein secretion ( 75 ). Palmitoylation affects cellular protein dynamics and differential regulation ( 76 ). Myristoylation affects plasma targeting, subcellular tracking, and protein localization ( 77 ).…”
Section: Localization Structure and Enzymatic Activity Of Sirt6mentioning
confidence: 99%
“…These Ca 2+ handling proteins are susceptible to a range of post-translational modifications (PTMs) that significantly influence their operational characteristics, activity levels, degradation pathways, subcellular localization, and interactions with other cellular components. These intricate modifications encompass oxidative and reductive modifications, glycosylation, ubiquitination, and acylation [ 6–8 ]. Here, we summarize recent studies reporting the S-acylation of Ca 2+ transporters, detailing the biochemical assays used, the residues and enzymes identified, and the functional consequence of this PTM for calcium fluxes and cellular functions.…”
Section: Introductionmentioning
confidence: 99%